A Calculation Method for Static Hysteresis Loop and its Applications - Fu, Yu; Miao, Yu; Li, Xinhao; Zhao, Xiaojun; Qian, Ziyi; Wang, Haoming (Recent Advances in Electrical & Electronic Engineering, 2025)
BackgroundDue to experimental equipment limitations, it is usually difficult to measure the quasi-static hysteresis loop at extremely low frequencies, which inevitably introduces errors in the static hysteresis model.ObjectiveThis study aims to propose a method for calculating the static hysteresis loops of grain-oriented silicon steel sheets so as to improve the accuracy of the static and dynamic hysteresis model.MethodsThe parameters n0 and V0 in the magnetic field strength expression of the excess loss are determined by the measured losses within the range of 0-100Hz. Subsequently, the dynamic components in the quasi-static hysteresis loops are eliminated. Furthermore, a dynamic hysteresis model is established based on the loss and field separation theory, which incorporates the inverse Preisach model.ResultsThe dynamic hysteresis loops of the grain-oriented silicon steel sheets are measured in the range of 8-250Hz and compared with the results of both the improved model and the original model.ConclusionExperimental results demonstrate the effectiveness and accuracy of the improved model. The proposed method for calculating static hysteresis loops has universal applicability and is meaningful for accurate simulation and prediction of magnetic properties in soft magnetic materials.
Keywords: hysteresis model